Pengaruh Kepuasan Konsumen dan Citra Merek, Kualitas Pelayanan Terhadap Keputusan Pembelian Produk Kosmetik Wardah - Rita Haju Kaesti; Puput Melati; Rayhan Gunaningrat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Wardah has built a reputation for itself as a manufacturer of premium, halal cosmetics in an effort to attract a wider audience and increase sales. Finding out how BPOM and Halal labels affect product quality and customer happiness among Wardah cosmetics customers is one goal of this study; another is to determine whether factors related to price influence the buying decision of those who purchase Wardah cosmetics. As part of the research, 105 people who regularly use Wardah cosmetics were asked to fill out a survey. Consumer satisfaction with Wardah cosmetics was shown to have a favorable and statistically significant effect on overall satisfaction. Furthermore, customer satisfaction with Wardah cosmetics was positively and significantly affected by the brand image variable. A similar favorable and statistically significant relationship existed between service quality and customer happiness with Wardah cosmetics. In addition, customer satisfaction with Wardah cosmetics was positively and significantly impacted by the following factors: product quality, brand image, and service quality.